Geoprocessamento aplicado na análise do uso e ocupação do solo no extremo noroeste da Bacia Hidrográfica do Guamá - PALMEIRA, Thais dos Santos (2022)
The present work is directed to the studies of the socio-environmental interactions in the municipalities inserted in the lower course of the Guamá watershed, specifically those located in its extreme northwest, highlighting the following municipalities: Belém; Ananindeua; Marituba; The face; Benevides; Bujaru; Concordia do Pará; Inhangapi and Santa Isabel. The research aimed to identify and analyze the current situation of the extreme northwest of the Guamá River Basin, making an integrated analysis of the existing environmental components and identifying the use and occupation of the land, through the geoprocessing technique with the use of Landsat satellite images. , of the sensors (TM and OLI). It was possible to observe that the studied area undergoes changes in its natural landscape, mainly due to agricultural and livestock activities, through the data collected it was noticed that this process of use and occupation has generated great environmental impacts, such as the reduction of natural vegetation cover in northwest region of the Guamá watershed. Thus, the use of geotechnologies was extremely important in the mapping, with the use of geoprocessing it was possible to generate thematic maps, which ensured efficiency and speed in the process of manipulation and treatment of data to obtain the results.